Local atomic structure of Zr–Cu and Zr–Cu–Al amorphous alloys investigated by EXAFS method - Antonowicz, J.; Pietnoczka, A.; Zalewski, W.; Bacewicz, R.; Stoica, M.; Georgarakis, K.; Yavari, A.R. (Journal of alloys and compounds, 2011)
▶ Coordination number, interatomic distances and mean square atomic displacement in Zr–Cu and Zr–Cu–Al glasses. ▶ Icosahedral symmetry in local atomic structure. ▶ Deviation from random mixing behavior resulting from Al addition. We report on extended X-ray absorption fine structure (EXAFS) study of rapidly quenched Zr–Cu and Zr–Cu–Al glassy alloys. The local atomic order around Zr and Cu atoms was investigated. From the EXAFS data fitting the values of coordination number, interatomic distances and mean square atomic displacement were obtained for wide range of compositions. It was found that icosahedral symmetry rather than that of corresponding crystalline analogs dominates in the local atomic structure of Zr–Cu and Zr–Cu–Al amorphous alloys. Judging from bonding preferences we conclude that addition of Al as an alloying element results in considerable deviation from random mixing behavior observed in binary Zr–Cu alloys.